Topical use of human breast milk for diaper rash in infants, “This paper has been withdrawn” - Penjvini, Susan; Shahsawari, Siroos; Gazerani, Farideh; Abdolkawand, Sohaila (International Journal of Advanced Nursing Studies, 2012)
This paper has been withdrawn.